Modification of surface pyrolytic graphite by nitrogen and argon plasma on air; Energy Fluxes and Radiation Effects (EFRE-2016) - Bureyev O. Oleg; Zhidkov M. Mihail; Kolobov Yu. Yuri; Ligacheva E. Elena; Ligachev A. Alexandr; Potemkin G. V. Gely Valerjyanovich; Stepanenko V.; Imamttdinov A. (2016, 2016)
Title screen